Lactoferrin Modulates Radiation Response Under Hypoxic Conditions, Possibly Through the Regulation of ROS Production in a Cell Type-Specific Manner - Daitoku Murakami; Takahiro Fukazawa; Michihito Kyo; Mutsumi Miyauchi; Shigehiro Ono; Tomonao Aikawa; Nobuyuki Hirohashi; Keiji Tanimoto (Antioxidants)
Lactoferrin (LF) is an iron-binding glycoprotein of the transferrin family and has been suggested to have a variety of biological functions, including anticancer activity. However, the effects of LF and its mechanisms in anticancer therapies, especially in radiotherapy against cancer cells under hypoxic conditions, are not well-determined. In this study, we focused on the molecular mechanisms of LF functions in cells under hypoxic conditions. High-dose LF treatment showed cytotoxic activity in a variety of cells, including both non-cancer and cancer cells. Interestingly, hypoxic treatment increased the sensitivity to LF in some cancer cells but decreased it in non-cancer cells. LF treatment also altered sensitivity to radiation treatment: LF significantly increased the viability of irradiated KD non-cancer cells under hypoxic conditions but decreased that of HSC2 cancer cells. These effects were only observed when LF was treated within 3 h of irradiation, but not before irradiation. Importantly, knockdown of HIF1A counteracted these effects in both cell lines. Measurements of ROS activity showed that LF decreased ROS production in KD cells but increased it in HSC2 cells, resulting in a decrease in γH2AX foci in KD cells but an increase in HSC2 cells. RNA-seq and gene set enrichment analysis showed that LF treatment regulated gene expression related to the cell cycle, apoptosis, inflammation, and the NRF2 antioxidant signaling pathway. Quantitative RT-PCR confirmed the downregulation of the pro-apoptotic gene ASC in KD cells and the NRF2-regulated genes in HSC2 cells by LF treatment. Knockdown experiments confirmed the role of ASC in irradiated KD cells and NRF2 in irradiated HSC2 cells with LF treatment. In conclusion, lactoferrin was shown to affect radiation treatment by regulating apoptosis and NRF2 signaling in a cell type-specific manner under hypoxic conditions, suggesting its potential application as a protector or sensitizer for radiation therapy.